Design and Build a Tourism Website Using Shopify Framework - Fachriza Habibi; Isnaini Faiz Qathrunada; Thamita Anggraini (Hanif Journal of Information Systems, 2023)
Tourism activities are currently in great demand by travelers who are usually carried out on holidays or spare time. Travelers often experience confusion in choosing tourist attractions to visit and it is also difficult to book places such as hotel rooms, etc. due to a lack of telephone number information. For this reason, based on the existing problems, this research will design a tourism website using the shopify framework. The purpose of this research is to help make it easier for travelers to find where to visit tourist attractions and to be able to make bookings online so they don't worry about running out of places such as hotel rooms when they arrive at tourist sites. In this study, the Research and Development (R&D) method was used in designing and building a tourism website using the shopify framework. This research succeeded in creating a tourism website using the shopify framework which can be accessed by 2 different parties with a special page, namely the customer on the facilities menu page to place product orders and the admin on the admin page to view and confirm every incoming order, add sales products, change product prices or product images, change or add product descriptions and add new features.